2012
DOI: 10.1111/j.1758-2229.2012.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability of the mouse gut microbiota in relation to innate and adaptive immunity

Abstract: Gut microbial community properties of mammals are thought to be partly shaped by a combination of host immunity and environmental factors, but their relative importance is not firmly established. To address this gap, we first characterized the faecal bacteria of mice with a functioning immune system (wild-type, WT), mice with defective immune responses (CD45), mice lacking an adaptive immune system (RAG), and mice with both immune dysfunctions (45RAG). Using fingerprinting of 16S rRNA genes, we observed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 60 publications
2
76
0
Order By: Relevance
“…À / À mice (Dimitriu et al, 2013), but a direct effect of adaptive immunity on microbiota was not demonstrated through adoptive transfer. In addition, whether the microbiota differences between mouse strains were affected by animal age and sampling site was unknown.…”
Section: Discussionmentioning
confidence: 92%
“…À / À mice (Dimitriu et al, 2013), but a direct effect of adaptive immunity on microbiota was not demonstrated through adoptive transfer. In addition, whether the microbiota differences between mouse strains were affected by animal age and sampling site was unknown.…”
Section: Discussionmentioning
confidence: 92%
“…22 In addition, Dimitriu et al also reported differences in bacterial community composition in faeces between WT mice and mice lacking adaptive immunity (CD45, RAG and 45RAG double knock-out) as analyzed by Principal coordinates analysis (PCoA) plots of bacterial community composition (T-RFLP fingerprints). 36 Interestingly, some bacterial species (and possible pathobionts) were only detected in the CD45 knockout mice, such as Alcaligenaceae and Helicobacteraceae. 36 In contrast, thymectomy of tadpoles (Xenopus laevis), a model in between zebrafish and higher vertebrates, did not result in differences in microbial composition.…”
Section: Discussionmentioning
confidence: 99%
“…36 Interestingly, some bacterial species (and possible pathobionts) were only detected in the CD45 knockout mice, such as Alcaligenaceae and Helicobacteraceae. 36 In contrast, thymectomy of tadpoles (Xenopus laevis), a model in between zebrafish and higher vertebrates, did not result in differences in microbial composition. 37 Although, Rag-deficiency and thymectomy cannot directly be compared, further investigation into this difference might yield clues concerning the mechanism by which T cells regulate microbial composition independently of B cells in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, sham-inoculated glands were only occasionally sterile. Molecular identification of the bacteria isolated from these glands suggests they originate from the pups, as they are closely related to the commensal microbiota (Martin et al, 2004) from the murine gut and respiratory system (Rodrigue and Lavoie, 1996;Shim et al, 2009;Dimitriu et al, 2013). These bacteria were retrieved in limited number compared with the inoculum and are therefore not considered to have influenced our results to a large extent.…”
Section: Experiments 2: Imi Of Mice With Different Cns Strainsmentioning
confidence: 95%